Unveiling Shared Meanings: A Symbolic Synthesis of Temple Pinnacle Ornaments Across Asia - Ni Kadek, Ayu Lestari; I Nyoman Widya Paramadhyaksa; Ema Yunita Titisari; I Gusti Agung Bagus Suryada (International Journal of Environment, Architecture, and Societies, 2025)
Hindu and Buddhist temples across Asia are renowned for their distinctive pinnacle ornaments, which, despite varying names and forms across regions, share a profound equality of symbolic meaning. This qualitative study employs a comparative approach, analyzing diverse architectural examples to uncover and interpret the underlying symbolic meanings of these ornaments on various Hindu and Buddhist temple structures in Asia, such as vat shrines in Cambodia, wa̋t in Thailand, mandir in India and Nepal, pagoda in Japan, and temple and meru in Indonesia and Bali. The findings show that (a) in the human body, the ornament at the top of the temple can be interpreted as the crown of the head element; (b) the ornament at the top of the temple can be interpreted as the top of the mountain; (c) the existence of the ornament at the top of the temple building can be compared to the heaven at the top of Mount Meru; and (d) the ornament at the top of the temple is realized as small, abstract motifs, and has four similar faces. These shared symbolic interpretations underscore a profound underlying cosmological and philosophical unity within Hindu and Buddhist architectural traditions across the Asian continent.